Macrozoobenthos Diversity as Bioindicator of Water Quality in the Namu Sira-Sira River, Durian Lingga Village, Langkat Regency, North Sumatra - Annisa Balqish; Melfa Aisyah Hutasuhut; Zahratul Idami (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Macrozoobenthos plays a role in biomonitoring of a body of water, because its life tends to settle in the bottom sediments of waters. The purpose of this study was to determine the diversity of macrozoobenthos as a bioindicator of water quality in the Namu Sira-Sira River, Durian Lingga Village, Langkat Regency, North Sumatra. Sampling was conducted at three stations. Station 1 (Upstream River), Station 2 (Bathing Tourism), and station 3 (Downstream River). This research method uses purposive sampling. Sampling of macrozoobenthos at the bottom of the river using a surber net measuring 30 x 30 cm. The results showed that macrozoobenthos found in Namu Sira-Sira River consisted of 7 orders of 18 families and 23 species. Kenaekargaman index (H') Macrozoobenthos in the Namu Sira-sira River at 3 stations that ranged from 1.42-1.60 (medium diversity category), the level of evenness (E) ranged from 0.72 -0.81 (fairly evenly distributed) and the Dominance index 0.14 - 0.21 (no dominant species). Water quality in the Namu Sira-sira river with a value of 3.97-4.57 (good)